Factors Associated With Weight, Length, and BMI Change in Adolescents' Offspring in Their First Year of Life - Sámano, Reyna; Chico-Barba, Gabriela; Martínez-Rojano, Hugo; Hernández-Trejo, María; Birch, Mery; López-Vázquez, Maribel; García-López, Gabriela Eurídice; Díaz de León, Jesús; Mendoza-González, Cynthia Vanessa (Frontiers in Pediatrics, 2021)
Background: Young maternal age is associated with negative outcomes at birth and with offspring’s growth. In low- and middle-income countries, adolescents’ offspring growth little has been studied. Objective: To determine the association of maternal sociodemographic characteristics with weight, length, and BMI change in adolescents’ offspring in their first year of life. Methods: This is a one-year follow-up study that included adolescent mothers and their offspring from 2010 to 2017. The infant anthropometric variables were performed at birth, 3, 6, and 12 months. Maternal health, pregnancy, and social variables were evaluated as well as birth outcomes. Crude, percentage, Z score, and percentile changes of weight, length, and BMI were evaluated from birth to 1-year-old. Statistical analyses were adjusted by maternal chronological age, socioeconomic status, breastfeeding duration, the timing of introduction of complementary feeding, among other variables. Results: We examined 186 dyads (mother-infant). The median maternal age was 15.5 years, and the mean pre-pregnancy BMI was 20. The mean gestational age was 39.1 weeks for infants, birth weight was 3,039 g, and length at birth was 49.5-cm. Maternal chronological age, the timing of introduction of complementary feeding, socioeconomic status, and maternal occupation were associated with offspring’s weight gain at 12 months. Length gain was associated with exclusive breastfeeding. Socioeconomic status and occupation were associated with offspring’s BMI change. When performing adjusted multivariable analyses, weight and length at birth were associated weight and BMI at 12 months. Conclusions: Weight at birth may negatively predict infant’s weight and BMI changes at 12 months, while length at birth may positively predict the changes. Maternal chronological age, socioeconomic level, occupation, and the timing of the introduction of complementary feeding were associated with the weight change. Only exclusive breastfeeding was associated with length Z-score change in adolescents’ offspring in their first 12-months of life.